PENERAPAN SISTEM E-BUPOT UNIFIKASI UNTUK PELAPORAN PPH PASAL 23 - Achmad Hidayat, Rovino; Diarany Sucahyati (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Tax management is a crucial aspect in maintaining the stability and sustainability of a country's economy. Income Tax (PPh) is the main source of revenue for the government. Income Tax Article 23 is a tax that is deducted from income such as interest, royalties and dividends. Prior to the adoption of Unification e-Bupot, all administrative processes were carried out manually, which was often prone to errors and took a long time. This research aims to analyze the Unification e-Bupot system in reporting Income Tax Article 23 (PPh Article 23). E-Bupot Unification is an electronic innovation that facilitates online tax withholding and reporting, aiming to reduce fraud, increase accuracy and simplify the obligations of tax withholding agents. This research uses a qualitative descriptive approach by collecting data through observation, direct interviews and literature study. The analysis results show that e-Bupot Unification provides significant benefits in increasing taxpayer compliance and tax administration efficiency. However, technical challenges such as bugs in the system are also a major concern that needs to be addressed to improve the overall performance of this application.